AN ANALYSIS OF GRAMMATICAL ERRORS IN THE TRANSLATION MADE BY THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION PROGRAM - Shafira Khoirunida (JELLT (Journal of English Language and Language Teaching), 2019)
This research analyzed the types of grammatical error that occur in the translations made by the fourth semester students. The objectives of this research are 1) to describe the types of grammatical errors and 2) to identify the most dominant types of grammatical errors that occured in the translations made by the fourth semester students in English Education Program at UST in Academic Year 2017/2018. This research applied descriptive qualitative research method. The data were collected using a test. In the analysis process, the theory proposed by Dulay was applied including the identification, description, explanation, and evaluation of the occurrence of errors. There were four types of grammatical error found in students’ translation made by the fourth-semester students, they were omission, addition (double marking, regularization, simple addition), misformation (regularization, archi-forms, alternating form), and misordering errors. Meanwhile, the total data were about 116 errors which showed that the students made 80 times (69%) of omission errors, 27 times (23%) of misformation error, 8 times (7%) of addition error, 1 times (1%) of misordering error. The most dominant type of grammatical error that occured in the student’s translation was omission.